Social embedding and the integration of markets: An opportunity for transnational trade union action or an impossible task? - Otto Jacobi; Maria Jepsen; Berndt Keller; Manfred Weiss (Hans-Böckler-Stiftung, 2007)
Increasing signs seem to indicate that, in the areas of both politics and thought, the age of neoliberal supremacy is approaching its end. An ideology based exclusively on the free play of the market is bound, ultimately, to lose its attraction. Growing inequality and social exclusion, with new forms of underclass suffering new forms of insecurity, cause the neoliberal conceptions to forfeit all moral credibility. Increasing conviction is attaching to the notion of social embedding, according to which transnational political and economic areas - such as the European Union - require democratic governance in order to foster social cohesion and environmental sustainability. The change in political climate has also reached the trade unions, whose members are becoming increasingly vocal in their rejection of shareholder capitalism. The trade unions have acknowledged that, on the other side of the nation state, they now have their second home in Europe. As such, they are developing new strategies for deployment in the European arena and seeking to make use of the opportunities offered by coordination of their policies at European level.
Keywords: 330; Marktwirtschaft; Soziale Sicherheit; Internationale Arbeitsbeziehungen; Tarifverhandlungen; EU-Sozialpolitik; EU-Staaten; Welt; Deutschland